Lipid-Lowering Effects of Carob Extracts (Ceratonia siliqua): Proposed Mechanisms and Clinical Importance - Nemet, Marko; Vasilić, Milica; Tomas, Ana (Frontiers in Pharmacology, 2022)
The global prevalence of dyslipidemia (elevated plasma levels of total cholesterol, LDL-Cholesterol, triglycerides, and lower plasma levels of HDL-Cholesterol) is constantly on the rise. Lately, carob pulp has been recognized as an effective natural product for the treatment of dyslipidemia. The two main components of the carob pulp, polyphenols, and insoluble fiber are believed to have beneficial effects on lipid metabolism. Studies on humans and animals confirmed its lipid-lowering effects. Several mechanisms have been proposed to explain this phenomenon, namely by affecting three organ systems: 1) gastrointestinal tract, 2) liver and 3) adipose tissue. Also, carob products have antioxidative, anti-inflammatory, and vascular-protective activity.